An exploration of sanitation-related decision-making, leadership, collective action, and freedom of movement among women in urban Tiruchirappalli, India - Doma, Rinchen; Patrick, Madeleine; Conrad, Amelia; Ramanarayanan, Vinod; Arun, Srishty; Sinharoy, Sheela S.; Caruso, Bethany A. (Frontiers in Water, 2023)
Introduction Sanitation research in India has emphasized the disproportionate burden that unsafe and inadequate WASH can have on women and girls. However, there is a gap in research exploring women's agency in relation to their sanitation experiences, and agency is an integral domain of their empowerment. Methods Cognitive interviews related to sanitation and empowerment were conducted with women in three life stages in India to validate survey tools that measure urban sanitation and women's empowerment; this paper is a secondary thematic analysis of qualitative data generated from 11 cognitive interviews in Tiruchirappalli, India, that focus on agency, specifically the sub-domains of decision-making, leadership, collective action, and freedom of movement. Women had the freedom to move to and from sanitation facilities and initiatives, with no restrictions from household members. Results We observed differences at the household and community levels with women voicing more confidence, as well as the responsibility, to make sanitation-related decisions in the household than at the community level. Women mentioned strong trust and belief in women's sanitation-related leadership capabilities and support for women-led sanitation initiatives. However, many did not hold leadership positions themselves due to various limitations, from gendered responsibilities to women's lack of self-confidence. Women also discussed anecdotes of collectively working with other women toward improving the local sanitation environment. Discussion This analysis highlights the value of strong trust and confidence among women in their ability to make important sanitation-related decisions at all levels of society. Maintaining and strengthening trust in female community members and highlighting women-led groups' achievements in the sanitation space should be prioritized. Community spaces must incorporate provisions that encourage women to share sanitation-related opinions in an environment that respects their engagement. WASH programming must engage with authority figures, leaders, and officials when seeking to increase women's agency and involvement with sanitation-related issues.